Perspectives on the transformation of microfinance institutions in Kenya into regulated status under the Microfinance Act. - (:unkn) unknown (My University, 2015)
The government's move to regulate Microfinance Institutions (MFIs) was primarily to create an enabling environment for MFIs to maximize outreach on a population without access to financial services in Kenya. The Microfinance Act, 2006 will allow qualifying microfinance institutions to transform into deposit-taking institutions. The Act lays the legal and regulatory framework of licensing and supervision of microfinance institutions. The primary objective of this thesis was to assess the prevailing institutional capacity and preparedness of the existing microfinance institutions to transform into deposit taking MFIs. Secondly, was to establish the perception of microfinance practitioners on the appropriateness of the legislation and regulations for the microfinance industry in Kenya. The study employed surveyed methodology to explore issues such as institutional capacity and preparedness of microfinance institutions. A researcher constructed questionnaire was administered to elicit responses from the microfinance institutions that are members of the Association of Microfinance Institutions (AMFI). Face-to-face interviews with executives of microfinance institutions were conducted to supplement the questionnaire and also for an in-depth understanding and analysis of certain key aspects of the research. findings of the study suggest that there are considerable challenges to the transition from informal to formal institutions. the institutions expressed concern with respect to certain regulatory requirements in microfinance legislation and regulations that make the costs of implementation quite high. the requirements that were considered to be most difficult and by extension considered inappropriate for the microfinance industry were the requirements for business premises, loan loss provisioning and disclosure and reporting requirements. the branch infrastructure and overall cost of transformation, in particular modernization of Management Information Systems (MIS) are considered quite significant, especially for smaller or rural MFIs which will have to incur additional costs of upgrading their MIS.
Partial fulfillment for award of Master of Commerce
The government's move to regulate Microfinance Institutions (MFIs) was primarily to create an enabling environment for MFIs to maximize outreach on a population without access to financial services in Kenya. The Microfinance Act, 2006 will allow qualifying microfinance institutions to transform into deposit-taking institutions. The Act lays the legal and regulatory framework of licensing and supervision of microfinance institutions. The primary objective of this thesis was to assess the prevailing institutional capacity and preparedness of the existing microfinance institutions to transform into deposit taking MFIs. Secondly, was to establish the perception of microfinance practitioners on the appropriateness of the legislation and regulations for the microfinance industry in Kenya. The study employed surveyed methodology to explore issues such as institutional capacity and preparedness of microfinance institutions. A researcher constructed questionnaire was administered to elicit responses from the microfinance institutions that are members of the Association of Microfinance Institutions (AMFI). Face-to-face interviews with executives of microfinance institutions were conducted to supplement the questionnaire and also for an in-depth understanding and analysis of certain key aspects of the research. findings of the study suggest that there are considerable challenges to the transition from informal to formal institutions. the institutions expressed concern with respect to certain regulatory requirements in microfinance legislation and regulations that make the costs of implementation quite high. the requirements that were considered to be most difficult and by extension considered inappropriate for the microfinance industry were the requirements for business premises, loan loss provisioning and disclosure and reporting requirements. the branch infrastructure and overall cost of transformation, in particular modernization of Management Information Systems (MIS) are considered quite significant, especially for smaller or rural MFIs which will have to incur additional costs of upgrading their MIS.
Keywords: Microfinance -- Legislation; Microfinance Act, 2006; Microfinance -- Kenya; Business Environment -- Small Business